Smart Bike Parking Station Menggunakan RFID Berbasis Internet of Things - Rafli Permana; Rivaldi Adi Sofian; Sri Danaryani; Shita Fitria Nurjihan (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2025)
In this modern era, students' interest in using bicycles as a means of transportation is decreasing due to various factors, such as traffic congestion, limited storage facilities, and parking security risks. To overcome these problems and encourage the use of bicycles as a more environmentally friendly means of transportation, innovative solutions are needed. Smart Bike Parking Station was developed to improve the safety and comfort of bicycle parking, especially in the campus environment. The Smart Bike Parking Station application utilizes Firebase as a database to store user information and manage the parking system. The login process uses Firebase Authentication, while data from the parking sensor is monitored through the Firebase Realtime Database. This system is also equipped with RFID technology for access control, ensuring that only registered bicycles can enter and exit the parking area. In addition, this application allows monitoring of the number of parking slots in real time and provides automatic notifications to users in the event of a theft attempt. The implementation of this system is supported by hardware such as an ESP32 microcontroller, vibration sensor, buzzer, motor driver, LED, and LCD, all of which are connected through an IoT platform with Google Firebase. Quality of Service (QoS) testing of the internet network used showed an average throughput of 7.24 Kbps, packet loss of 0%, an average delay of 346 ms, and an average jitter of 346 ms. With this system, it is hoped that more students will switch to using bicycles to go to campus, so that they can reduce the use of motorized vehicles and support efforts to reduce air pollution.